An Investigation of Foreign Language Anxiety among Sudanese EFL Students - Adil Ishag; Gamar Albooni (Journal of Linguistics and Language Teaching)
Foreign language anxiety has a debilitative and detrimental effect on the different stages of the language learning processes. The present study investigates the relationship between foreign language anxiety and students’ achievement in English, and examines gender differences and the most common sources of anxiety. 156 undergraduate EFL Sudanese students participated in the empirical investigation. A modified version of the Foreign Language Classroom Anxiety Scale was used, in addition to students’ Grade Point Average (GPA) as an indicator of language achievement. The results showed that foreign language anxiety decreased as language achievement increased. Furthermore, the fear of negative evaluation is reported to be the most prevalent source of anxiety, followed by communication apprehension. A number of suggestions are proposed in order to minimise students’ anxiety in the foreign language.